2009
DOI: 10.1089/ten.teb.2009.0139
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cements and Their Potential Use in a Mandibular Endoprosthesis

Abstract: Bone cement was first used in the 1950s. Since then many modifications have been made and alternatives developed to the original polymethylmethacrylate (PMMA) cement. In view of the use of bone cement in a novel mandibular endoprosthetic system, we performed a review of the current literature on this material. Different cements are described and their potential use in a mandibular endoprosthetic system discussed. The PMMA-based cements are currently the most suitable choice. Plain PMMA has the longest track re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 161 publications
(114 reference statements)
0
20
0
Order By: Relevance
“…63 Despite these findings, a number of studies exist that report no complications with solid PMMA use in craniofacial applications. 12,35,64,65 Porous PMMA, as previously mentioned, has also been investigated in animal studies and limited clinical use. In a long-term study in guinea pigs comparing porous and solid PMMA implanted in the hypodermis, van Mullem et al reported implant extrusion occurred in 4/36 solid implants and none of the porous implants.…”
Section: Discussionmentioning
confidence: 99%
“…63 Despite these findings, a number of studies exist that report no complications with solid PMMA use in craniofacial applications. 12,35,64,65 Porous PMMA, as previously mentioned, has also been investigated in animal studies and limited clinical use. In a long-term study in guinea pigs comparing porous and solid PMMA implanted in the hypodermis, van Mullem et al reported implant extrusion occurred in 4/36 solid implants and none of the porous implants.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium phosphate cement (CPC) possessed self-setting, moderate compressive strength even in loading sites and highly biocompatibility properties. It has been extensively studied and clinically used as bone substitute materials [13][15]. Recently, it was explored that CPC could facilitate the growth and differentiation of hDPCs in vitro; however, the potential of complexes with hDPCs and CPC for mineralized tissue formation need to be systematically investigated in vivo [16].…”
Section: Introductionmentioning
confidence: 99%
“…Self-setting CPC materials are widely used for orthopedic and dental applications and have the potential to stimulate osteogenesis (11). The self-setting, moderate compressive strength even in loading sites and highly biocompatibility properties (12) suggest that CPC is superior to pure CH, which means that this material may have applications in pulp capping to induce reparative dentin formation or as a lining material (13).…”
mentioning
confidence: 99%